PENGARUH KOMPETENSI, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI KPU KABUPATEN BANYUASIN - Bahrial Syah; Luis Marnisah; Fakhry Zamzam (Integritas Jurnal Manajemen Profesional (IJMPRO), 2021)
This study aims to analyze how competence, compensation and work motivation jointly affect the performance of KPU employees in Banyuasin Regency. The General Election of Banyuasin Regency used quantitative methods, using a saturated sampling sample in the study of 20 employees. In this study, the types of data used are primary data and secondary data. Data collection techniques using questionnaires, interviews, observation and documentation. Hypothesis testing through t test and F test using SPSS analysis tools. The results of data processing using SPSS 20, using the t test that t counts 4,330> t table 2.003 There is an influence of competence on performance; that t count 4.181> t table 2.003 positive and significant effect of compensation on performance; t count 4.469> t table 2.003 there is a positive and significant influence of motivation on performance; and F count 34.356> F table 4.883 and a significance level of 0.00 <0.05, that there is a positive and significant effect on the competency, compensation and motivation patterns together on performance, with a determination coefficient of 77.5%, the rest is influenced by other variables. The conclusion of the research is that competence, compensation and motivation have a positive and significant effect on performance either partially or simultaneously. Strategies to improve employee performance at the KPU Banyuasin Regency can be done by first increasing employee motivation to increase broad knowledge of knowledge in supporting work implementation, then increase. competence to be consistent in having a good attitude with colleagues.